2022
DOI: 10.1080/14760584.2023.2143347
|View full text |Cite
|
Sign up to set email alerts
|

Expert review of global real-world data on COVID-19 vaccine booster effectiveness and safety during the omicron-dominant phase of the pandemic

Abstract: Introduction: COVID-19 vaccines have been highly effective in reducing morbidity and mortality during the pandemic. However, the emergence of the Omicron variant and subvariants as the globally dominant strains have raised doubts about the effectiveness of currently available vaccines and prompted debate about potential future vaccination strategies. Areas covered: Using the publicly available IVAC VIEW-hub platform, we reviewed 52 studies on vaccine effectiveness (VE) after booster vaccinations. VE were repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 104 publications
1
23
0
Order By: Relevance
“…Our study found that the three vaccine types used for boosting in Thailand, P zer-BioNTech, Moderna and ChAdOx1 nCoV-19, offered similar protection against severe COVID-19 outcomes. Comparable protection from ChAdOx1 nCoV-19 and P zer-BioNTech against infection, hospitalization, ICU admissions and deaths, has been previously reported [12,20,22,23]. Our ndings corroborate this evidence and supports the use of mRNA vaccines and viral vector vaccines as booster vaccines, providing much needed exibility to incorporate different vaccines into schedules according to local supply and logistical considerations.…”
Section: Discussionsupporting
confidence: 86%
“…Our study found that the three vaccine types used for boosting in Thailand, P zer-BioNTech, Moderna and ChAdOx1 nCoV-19, offered similar protection against severe COVID-19 outcomes. Comparable protection from ChAdOx1 nCoV-19 and P zer-BioNTech against infection, hospitalization, ICU admissions and deaths, has been previously reported [12,20,22,23]. Our ndings corroborate this evidence and supports the use of mRNA vaccines and viral vector vaccines as booster vaccines, providing much needed exibility to incorporate different vaccines into schedules according to local supply and logistical considerations.…”
Section: Discussionsupporting
confidence: 86%
“…reported that the real-world evidence from different COVID-19 vaccines (parent strain) supports the completion of primary series and booster vaccinations where appropriate, especially to restore waning vaccine effectiveness against the more infectious Omicron variant and protect populations from severe outcomes, hospital admissions, and longer lasting post-COVID-19 complications, as well as mortality. 12 Considering this, booster doses are recommended at about 4–6 months or later after completion of primary immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the three vaccine types used for boosting in Thailand, Pfizer-BioNTech, Moderna and ChAdOx1 nCoV-19, offered similar protection against severe COVID-19 outcomes. Comparable protection from ChAdOx1 nCoV-19 and Pfizer-BioNTech against infection, hospitalization, ICU admissions and deaths, has been previously reported [ 12 , 20 , 23 , 24 ]. Our findings corroborate this evidence and supports the use of mRNA vaccines and viral vector vaccines as booster vaccines, providing much needed flexibility to incorporate different vaccines into schedules according to local supply and logistical considerations.…”
Section: Discussionmentioning
confidence: 65%